On the solution of a one-dimensional stochastic differential equation with singular drift coefficient - Kulik, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We determine generalized diffusion coefficients and describe the structure of local times for a process defined as a solution of a one-dimensional stochastic differential equation with singular drift coefficient.